Standardized Approach to the Analysis of the Sustainability of the Organization Activity - Elena B. Gerasimova (Учёт. Анализ. Аудит)
Subject. Currently, the development of the analysis of business performance - economic analysis - is connected with the transition to a new paradigm of the analysis. The search for a new paradigm of the activity analysis of the economic entities is associated with bridging the gap between the degree of elaboration of the theory and the methodology of economic analysis and the quality of analytical procedures in economic entities. The insufficient quality level of the analysis reduces the confidence in economic agents from the interested parties. Purpose. The paper aims to develop the principles of organization, functioning and the development of standardization system of the analysis of business performance. Methodology. In order to solve the set tasks there were used the methods of research (analysis and synthesis), comparative analysis, and the method of analogies. The research is built on the study of relevant economic literature and on the method of structural analysis. Results. On the basis of the analysis there were obtained the following results. Result 1. There were identified the reference points of the development of a modern economic entity - the increased sustainability of its activities and the quality improvement of the activities through the implementation of the standardization system. Result 2. The sustainability of the economic entity as the object of standardization of the analysis should be seen as a set of expert estimations of the stability conditions of the economic system for a certain period of time. Taking this into account standardization is becoming the way to provide the sustainability of the operation condition of the system. Result 3. Standardization of the analysis of business performance is based on the Russian legislation regulating the standardization and all the areas associated with carrying out analytical procedures such as accounting, auditing, internal control and others. The standard of business performance analysis is proposed to be developed as the company standard. Result 4. The system of standards of business performance analysis will enhance the quality of activities and the loyalty of stakeholders, and it will also reduce costs and risks. Conclusions. The development of the standardization system of the business performance analysis is a very promising direction aimed at improving the quality of business. Standardization of economic analysis opens up great opportunities in the sphere of improving the quality of activities of economic entities, regardless of the specific scope of the evaluation study application.